Improved corrosion resistance and antibacterial properties of composite arch-wires by N-doped TiO2 coating. Issue 69 (11th September 2017) - Liu, Jiming; Lou, Yixin; Zhang, Chao; Yin, Shuo; Li, Hongmei; Sun, Daqin; Sun, Xinhua
Abstract : In this paper, composite arch-wires (CAWs) coated with TiO2 and N-doped TiO2 nanocrystal thin films were fabricated. Abstract : In this paper, composite arch-wires (CAWs) coated with TiO2 and N-doped TiO2 nanocrystal thin films were fabricated. We found that the corrosion resistance and antibacterial properties of CAWs can be significantly improved by coating with the TiO2 nanocrystal thin film, especially using the N-doped TiO2 nanocrystal thin film, which is extremely important for their clinical application. The improved performances were confirmed by measuring potentiodynamic polarization curves and electrochemical impedance spectroscopy (EIS). The results revealed that N-doped TiO2 coated CAWs can prolong the wearing time and improve the security of the arch wire in the oral cavity. In addition, the antibacterial activities of the samples were tested against Streptococcus mutans by bacterial culture. It was found that the CAWs coated with N-doped TiO2 showed the highest antibacterial activity. Finally, the cytotoxicity of the samples was tested and evaluated, and the results showed that the CAWs modified with the N-doped TiO2 nanocrystal thin film have great potential in practical dental treatment.